Hyperbaric effects on heart rate in professional SCUBA divers in thermal water - Luigi Fattorini; Angelo Rodio; Tommaso Di Libero; Cristian Ieno; Giovanna Tranfo; Daniela Pigini; Alessandro Pinto; Enrico Marchetti (Frontiers Media S.A., 2024)
IntroductionDiving in SCUBA modality modifies human physiology in many ways. These modifications have been studied since Paul Bert in a seminal work. This area of research is very sensible to technological development. At now, it is possible to record heart rate (HR) continuously while diving. The study of HR changes in SCUBA diving at different depths in a constant temperature of thermal water is the objective of the present paper.Methods18 healthy subjects were enrolled and HR was recorded while SCUBA diving in thermal water at a constant temperature of 33.6∘ C in the deepest Italian pool at Montegrotto (Padova, Italy). Three depths were investigated: −20, −30 and −40 meters. The HR has been recorded with a Galileo SOL diving computer. The dive was subdivided into three phases: descent (DSC), steady on depth (STD), post-dive (RSF), and average HR was evaluated in each phase. Moreover, considering the DSC and STD time duration, a statistical linear regression of HR and relative parameters, intercept and slope, were here assessed.ResultsIn STD phase, HR slope obtained by regression decreased with depth. A significant difference was found between the slope during STD at −20 vs. −40 m (p ≤ 0.05).DiscussionPresent results emphasized different HR physiological adjustments among diving phases. Firstly, during the DSC, a rapid HR decrease is recognized as probably due to a vagal response; secondly, at STD, the inward blood redistribution requires another physiological adjustment. This latter is depth-dependent because of a reduction of cardiac variability. Present data highlight the important cardiac stress need to counteract the diving activity.